The effects of shift work on employee psychological wellbeing at the Cotton Company of Zimbabwe Ltd – Chinhoyi Business Unit. - Nancy, Chikuku (Midlands State University, 2017)
The purpose of the study was to establish the effects of shift work on employee psychological well being at the Cotton Company of Zimbabwe – Chinhoyi Business Unit. The study was guided by four objectives: to establish the effect of shift work on (a) on the circadian rhythm (b) physical health (c) social life and (d) personal growth. The study took a quantitative approach and used the exploratory descriptive design. The sample involved 161 participants from the ginnery department of Cottco Chinhoyi. Data was gathered using a self administered questionnaire and analysed at the descriptive level using summary statistics, frequencies and percentages. Findings were that (a) indeed shift work has negative effects on employee psychological well being. It was therefore concluded that, shift work affects the mental health, physical health, social lives and personal growth of employees which all encompasses psychological well being. The study finally recommended that; (a) shift work be used where and when necessary only (b) shift schedules and compressed work weeks be used to minimise health risks and social problems for the employees.